Studi Transmisi Gelombang Dengan Model Cylinder Concrete (Buis Beton) Breakwater Tenggelam Dengan Permodelan Fisik 2D - Manurung, Lodewick; Tugiono, Subuh; Zakaria, Ahmad; Purwadi, Ofik Taufik (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2022)
One way to prevent damage caused by sea waves is to build a breakwater to reduce wave energy before it reaches the coast. In making the breakwater model the author chose to make a breakwater model with a concrete cylinder because it can be obtained easily. The research data obtained wave height (H), wavelength (L), and wave period (T). From the research data obtained, it can be made a table of incident wave height (H0), transmission wave height (Ht), and wave transmission coefficient (Kt). In this study, 12 models were used, namely 4 breakwater devices with different breakwater widths (lb), and in each breakwater device using 3 heights of still water level clearance or ds (2 cm, 4 cm, and 6 cm). Based on the research, the smallest transmission coefficient value occurs in the longest lb with ds of 2 cm, which is 0.3567 and the largest transmission coefficient occurs in the shortest lb with ds of 6 cm, which is 0.7190. The biggest change in wavelength occurred in the longest lb with ds 2 cm, which was 21.57% and the smallest change occurred in the shortest lb with ds 6 cm, which was 9.23%. The biggest change in wave propagation speed occurred in the longest lb with ds 2 cm, which was 20.14% and the smallest change occurred in the shortest lb with ds 6 cm, which was 5.93%.